Amnestic Somnambulism and Nocturnal Eating Disorder Associated with Zolpidem Use as a Contributing Factor in Accidental Death. Issue 2 (June 2015) - Stump, Michael; Presnell, S. Erin
Zolpidem is a selective gamma-aminobutyric acid (GABA) receptor modulator used commonly in the treatment of insomnia. It is effective at initiating sleep and has primary effects similar to benzodiazepines. Zolpidem has gained some notoriety for its association with rare but unusual side effects of compulsive nocturnal activity with anterograde amnesia. Review of the literature documents zolpidem-associated nocturnal activities, which include walking, eating, and more complex activities such as house cleaning or driving. During these events, the sleeper may be able to converse and initially appear normal to an observer, but has limited, if any, recollection of the event. Other literature reviewing zolpidem-related deaths, hospital admissions, falls, and somnambulism found a high rate of concurrent alcohol and/or other drug use than when using Zolpidem alone. We present a case of a 67-year-old woman with a history of somnambulism and amnestic eating during the night after using Zolpidem who was found deceased on the pavement below her opened second story bedroom window. Autopsy revealed nonocclusive food substances in her airways, and head and neck trauma, consistent with a fall from the second story window. Toxicological analysis of peripheral blood revealed Zolpidem (69 ng/mL), pseudoephedrine (150 ng/mL), citalopram/escitalopram (400 ng/mL), and caffeine. Blood and vitreous ethanol concentrations were 194 mg/dL and 160 mg/dL, respectively. Given the decedent's nocturnal activity history associated with Zolpidem, Zolpidem use combined with ethanol was considered contributory to her death.